HOMAGE TO DYNAMISM: A CONTRIBUTION TO THE STUDY OF THE ICONOGRAPHY OF THE MACHINE CULT IN ORPHISM - Tasić, Dragan (RIHA Journal, 2017)
One of the trends in the early days of Cubism, Orphism was a style of painting that evolved in Paris during the period between 1911 and 1914. The orphists rejected the rigid principles of a non-abstract art and returned to “pure color” with the purpose of communicating their intense enjoyment. They were imbued with the new spirit and fascinated by the technological progress of the modern world. Robert Delaunay’s Homage to Blériot was painted in a state of extreme spiritual happiness, reflecting the whole atmosphere of the times. It is a testimony to the skills of the airplane constructors – the new heroes of a modern epic fantasy. World War I, however, spelled the end of the enthusiasm and optimism of the machine age.